Sakit dan Sehat, Perang dan Damai - T. Jacob, T. Jacob (Universitas Gadjah Mada, 1988)
This article described war as a colossal disaster, and nuclear war as the largest and the last manmade disaster. It exposed various levels of peace from total (utopian) peace to the absence of nuclear war. Differences in the concept of peace are brought forth from intraindividual peace to international peace. Threat to peace could and should be faced by various ways from the study of peace and war to peace or anti-war demonstrations. The nature of peace movements ranges from collecdon of signatures to the prevention of war preparation.Furtheremoie, the present world armament especially nuclear weaponry are described, followed by its effects on the health of mankind prior to their use, by diverting funds away from social and welfare sectors. The aim of war has become obscure because nothing can be achieved by nuclear war except total annihilation.Lastly, the effects of nuclear war are discussed, including the biological, medical, psychological, ecological and social economic consequences, and the article is concluded by enumerating the efforts of health professionals in preventing the extinction of mankind by unintended nuclear war.Key Words: consequences of nuclear war - Black Death - social responsibility of health professionals - war victims - chemical and microbiological weapons